VD_FINDINFO PPD 1/16 - 5/2017 vom 16. Januar 2017 - VD Tribunal cantonal (2017)
PRÉVOYANCE PROFESSIONNELLE, PARTAGESENS GÉNÉRAL, DIVORCE, INTÉRÊT MORATOIRE, INTÉRÊT RÉMUNÉRATOIRE | 122 CC, 22 LFLP, 25a LFLP, 7 OLP, 8a OLP, 12 OPP2